Prevalence and factors associated with depression in people living with HIV in sub-Saharan Africa: A systematic review and meta-analysis. - Charlotte Bernard; François Dabis; Nathalie de Rekeneire (PLoS ONE, 2017)
Depression, one of the most common psychiatric disorders, is two- to three-times more prevalent in people living with HIV (PLHIV) than in the general population in many settings as shown in western countries but remains neglected in sub-Saharan Africa (SSA). We aimed to summarize the available evidence on the prevalence of depression and associated factors according to the scales used and the treatment status in PLHIV in SSA. The pooled prevalence estimates of depression ranged between 9% and 32% in PLHIV on antiretroviral treatment (ART) and in untreated or mixed (treated/untreated) ones, with a substantial variability according to the measurement scale used and also for a given scale. Low socio-economic conditions in PLHIV on ART, female sex and immunosuppression in mixed/untreated PLHIV were frequently reported as associated factors but with no consensus. As depression could have deleterious consequences on the PLHIV life, it is critical to encourage its screening and management, integrating these dimensions in HIV care throughout SSA.